(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2012)
Arnold was as he said himself, “a liberal of theFuture” – a future which has not yet arrived. He lived through a period ofradical change – the Victorian age, and spoke more wisely of continuingproblems than our fashionable prophets of moral and social revolution or theirreactionary opponents. His eminence is due not only to his literary criticism,but also to his standing as a poet and general critic of English society andcivilization. Both in England and the United States- especially in academiccircles, his influence continues to be felt in a sizeable section of literaryintellectuals. Arnold might be called as Douglas Bush says, “an individualmixture of 18th century rationality, Romantic idealism, Victorian skepticismand modern existentialism…”1 (Bush, Matthew Arnold)